Encyclopedia of world biography. - Gale Research Inc. (Detroit Gale Research, 1998)
Presents brief biographical sketches which provide vital statistics as well as information on the importance of the person listed.
v. 1. A-Barbosa -- v. 2. Bardeen-Briand -- v. 3. Brice-Ch'i Pai-Shih -- v. 4. Chippendale-Dickinson -- v. 5. Diderot-Forbes -- v. 6. Ford-Grilliparzer -- v. 7. Grimke-Howells -- v. 8. Hoxha-Kierkegaard -- v. 9. Kilpatrick-Louis -- v. 10. Love-Micah -- v. 11. Michael-Orleans -- v. 12. Orozco-Radisson -- v. 13. Raffles-Schelling -- v. 14. Schiele-Stuart -- v. 15. Studi-Visser -- v. 16. Vitoria-Zworykin -- v. 17. Index -- 18. Supplement A-Z [1999] -- v. 19. Supplement A-Z [2000] -- v. 20. Supplement A-Z [2000] -- v. 21. Supplement A-Z [2001] -- v. 22. Supplement A-Z [2002] -- v. 23. Supplement A-Z [2004] -- v. 24. Supplement A-Z [2005] -- v. 25. Supplement A-Z [2005] -- v. 26. Supplement A-Z [2006] -- v. 27. Supplement A-Z [2007]
Rev. ed. of: The McGraw-Hill encyclopedia of world biography.
Supplement volumes include indexes with cumulative name listings.
Includes bibliographical references.
Keywords: Biography -- Dictionaries -- Juvenile literature; Biography